Kebijakan Perlindungan Hukum Pidana Bagi Anak dan Perempuan Korban Kekerasan Seksual - Prisko Yanuarius Djawaria Pare; Enjelina Wea; Claudia Yda (JURNAL RECHTENS, 2025)
Sexual violence today is always a threat that threatens the safety of life, one of which is children and women. The purpose of this study is to identify the factors causing violence, forms of violence and analyze criminal law protection policies to protect victims and combat perpetrators of sexual crimes. The type of research that is explored is normative juridical research by conducting an in-depth analysis of laws and regulations and doctrines in legal science. The results of the research achieved from this activity are as follows, it was found that the factors causing sexual violence are individual factors, relationship factors, community factors and environmental factors. The forms of violence that occur include; physical violence, psychological violence, sexual violence, economic violence, and cyber crime. Legal protection efforts provided include preventive legal protection and repressive legal protection.